2020
DOI: 10.1002/mus.27073
|View full text |Cite
|
Sign up to set email alerts
|

Ultra–high‐frequency ultrasound imaging of sural nerve: A comparative study with nerve biopsy in progressive neuropathies

Abstract: Introduction: Nerve ultrasound has been used increasingly in clinical practice as a complementary test for diagnostic assessment of neuropathies, but nerve biopsy remains invaluable in certain cases. The aim of this study was to compare ultra-high-frequency ultrasound (UHF-US) to histologic findings in progressive polyneuropathies. Methods: Ten patients with severe, progressive neuropathies underwent ultrasound evaluation of the sural nerve before nerve biopsy. Ultrasound data were compared with histologic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…High-frequency ultrasound imaging technology can clearly and intuitively display the nerve distribution and morphology of peripheral neuropathy in patients with type 2 diabetes, which provides very valuable information for the clinical diagnosis and treatment of the disease [ 14 ]. This study subsequently compared the changes in neuromorphology in patients with type 2 diabetes and peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-frequency ultrasound imaging technology can clearly and intuitively display the nerve distribution and morphology of peripheral neuropathy in patients with type 2 diabetes, which provides very valuable information for the clinical diagnosis and treatment of the disease [ 14 ]. This study subsequently compared the changes in neuromorphology in patients with type 2 diabetes and peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…However, these two tests all required specialist operations and are time-consuming, laborious, and costly, so it is limited in large-scale screening and routine examinations in diabetes clinics [ 11 13 ]. Clinical studies have shown that high-frequency ultrasound can clearly display the condition of peripheral nerves and accurately provide information on the course, distribution, echo, and anatomical relationship of surrounding tissues [ 14 ]. In recent years, high-frequency ultrasound has been widely used in the display of normal neural structures, the diagnosis of neuropathy, and the identification of tumors inside and outside the nerves [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Puma et al 43 in a retrospective observational study concluded that hyper‐echogenicity on UHFUS may be a marker of nerve inflammation in neuropathies. Boczar et al 44 presented a case report in which with the use of 70 MHz‐UHFUS they evaluated the nerve invasion of a lipofibromatous hamartoma not available on other imaging modalities.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al 39 ; Karakawa et al 40 Diagnosis and evaluation of pilomatricoma and aplasia cutis congenita Latham et al 41 Evaluate the vascular accesses in children for cannulation of peripheral arteries and central venous access Regensbruger et al 42 Evaluate nerve structure in congenital neuromuscular disorders Puma et al 43 Peripheral nerve and osteoarticular…”
Section: Clinical Evidence: Dermatological Settingmentioning
confidence: 99%
“…According to Härtig et al [ 6 ], hypoechogenic nerves in patients with chronic inflammatory demyelinating polyneuropathy (CIDP) reflect oedema and demyelination, whereas hyperechogenic nerves represent axonal damage with fibrous-scarring remodeling. In contrast, Puma et al [ 7 ] described increased inflammatory infiltrates in hyperechogenic nerves. Furthermore, echogenicity was described as highly variable even in healthy individuals [ 4 ].…”
Section: Introductionmentioning
confidence: 96%